2019
DOI: 10.1002/mgg3.526
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the p.[Arg74Trp;Val201Met;Asp1270Asn]/p.Phe508del CFTR mutation genotype in human native colon

Abstract: Background The impact of complex alleles on CFTR processing and function has yet not been investigated in native human tissue. Methods Intestinal current measurements (ICM) followed by CFTR immunoblot were performed on rectal biopsies taken from two siblings who are compound heterozygous for the CFTR mutations p.Phe508del and the complex allele p.[Arg74Trp;Val201Met;Asp1270Asn]. Results Normal and subnormal chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The two index cases were affected by mild CF. 19 Discordant CFTR biomarker phenotypes were noted for carriers of the p.Arg117His mutant. The three p.Phe508del /p.Arg117His compound heterozygotes in our cohort showed CFTR dysfunction in the CF range, whereas the p.Arg117His-7T homozygote exhibited normal CFTR activity consistent with a previous report of normal clinical features and normal CFTR activity in two homozygous p.Arg117His-7T adults.…”
Section: Cftr Activity Of Individuals With Cftr Genotypes Of Unknown mentioning
confidence: 99%
“…The two index cases were affected by mild CF. 19 Discordant CFTR biomarker phenotypes were noted for carriers of the p.Arg117His mutant. The three p.Phe508del /p.Arg117His compound heterozygotes in our cohort showed CFTR dysfunction in the CF range, whereas the p.Arg117His-7T homozygote exhibited normal CFTR activity consistent with a previous report of normal clinical features and normal CFTR activity in two homozygous p.Arg117His-7T adults.…”
Section: Cftr Activity Of Individuals With Cftr Genotypes Of Unknown mentioning
confidence: 99%
“…In our hands, such signals were regularly unmasked by PNgase digestion or peptide competition as false-positive immunoreactive signals not corresponding to the CFTR protein. Apart from the monoclonal CFTR antibodies provided by Tim Jensen, Chapel Hill via the antibody distribution program for this work [ 34 ], we also tested a collection of 10 customized rabbit polyclonal antibodies (Eurogentec) generated to detect CFTR [ 35 , 36 , 37 ] via immunoblotting. With three of these customized antibodies, we detected a lege artis CFTR signal from 16HBE14o- positive control lysates.…”
Section: Discussionmentioning
confidence: 99%
“…Normal (younger brother) and subnormal (older brother) chloride secretion measured by ICM were associated with normal CFTR protein formation and a fourfold decrease in its amount, respectively. Thus, the authors found differences in the same family in phenotypic manifestations with the same genotypes [ 37 ].…”
Section: The Influence Of Genetic Variants In the Composition Of A Co...mentioning
confidence: 99%